Invasive House (Rattus Rattus) and Brown Rats (Rattus Norvegicus) Threaten the Viability of Red-Billed Tropicbird (Phaethon Aethereus) in Abrolhos National Park, Brazil. (December 2014) - Sarmento, Raissa; Brito, Daniel; Ladle, Richard James; Leal da Rosa, Gustavo; Efe, Marcio Amorim
Destruction of nests and predation by introduced species are among the main factors responsible for seabird declines. The red-billed tropicbird ( Phaethon aethereus ) is a tropical, colonially nesting seabird whose distribution in Brazil is restricted to a small, isolated breeding colony located within Abrolhos National Park. This represents the southernmost population of the species in the western Atlantic, and is among the most southerly in its global distribution. Despite its isolation, the population on Abrolhos is threatened by egg predation by two invasive rat species: the house rat ( Rattus rattus ) and brown rat ( Rattus norvegicus). In this study we conduct a population viability analysis of P. aethereus in Abrolhos to estimate the potential long term impacts of the rats. Our results indicate that egg and chick predation by rats has the potential to quickly drive the Abrolhos tropicbird population into serious decline. Reducing this threat may require the urgent implementation of a rat control program.